Raindrop size distribution and vertical velocity characteristics in the rainband of Hurricane Bolaven (2012) observed by a 1290 MHz wind profiler. (March 2017) - Kim, Dong-Kyun; Lee, Dong-In
Abstract: Microphysics and vertical velocity characteristics between weak and strong rainband regions of Hurricane Bolaven were investigated primarily from 1290 MHz (UHF) wind profiler measurements on 27–28 August 2012. With a focus on regions with radar reflectivities greater than 30 dBZ below a melting level, raindrop size distributions (DSDs) and related rain parameters retrieved from profiler Doppler spectra were examined. Temporal variations in vertical structure and bright band from a widespread stratiform to a relatively narrow, intense rainband were examined as the rainbands move over the land in the southern coast of Korea. Based on vertical characteristics in radar reflectivity, Doppler velocity, and vertical air motion ( w ) profiles, the rainbands were classified into a stratiform (S) region with a strong bright band and mixed stratiform-convective (S-C) region with a weak or non-existent bright band. The retrieved w fields showed that updrafts were dominant in the mixed S-C region and downdrafts in the S region. More broad histograms in both radar reflectivity ( Z ) and mass-weighted mean diameter ( D m ) were found in the S period. Compared to the Z distribution, rain rate ( R ) was more widely distributed in the mixed S-C region than in the S region. This is largely because R values were more variable in association with stronger updrafts in this region since they depend on fall velocities of raindrops. Higher R and smaller D m mean values were analyzed within relatively strong updrafts in the mixed S-C period compared to those in the S period. Even when the w correction is applied, the mean D m was still slightly smaller in the mixed S-C region, indicating that there is a relatively larger number of small drops than those in the S region. Highlights: Characteristics in the mean vertical profiles are examined from vertically pointing radar measurements. Stratiform (S) and mixed stratiform-convective (S-C) regions showed noticeable difference in microphysics and vertical velocity characteristics. The Dm histogram showed that the mean Dm in the mixed S-C region is slightly smaller than that in the S region when vertical air motion effect is taken into account.